Quantitation of Leydig Cell in Testicular Biopsies of Gossypol Treated rats - Al Bayaty, Muhannad A. A. (The Iraqi Journal of Veterinary Medicine, 2005)
Leydig cell density was evaluated quantitatively in bilateral testicularbiopsies from twenty male rats of two equal groups Gossypol treated andcontrol. The method utilized for this quantitation is based on the determinationof total number of Leydig cells, Leydig cell clusters and seminiferous tubules inthe entire histological section of each biopsy and the calculation of the followingindices: mean Leydig cells per seminiferous tubule, mean Leydig cell clustersper seminiferous tubule and mean Leydig cells per cluster. A significant positivecorrelation between Leydig cells per tubule and Leydig cell clusters per tubulewas demonstrated. The results of indices curve showed shifted all the curves tothe right in Gossypol treated group, a significant reduction in plasmatestosterone levels of Gossypol treatment group as compared to control groupwhich is due to decrease in Leydig cells number, suggesting that determinationof Leydig cell clusters per seminiferous tubule in testicular biopsies is anobjective and clinically applicable method for quantitative evaluation of Leydigcell density and indirectly evaluated the secretary activity of the testicularLeydig cells. The results are attributed to the direct effect of Gossypol onsecretary site of testosterone in Leydig cells or presumably indirect disturbanceof hypothalamic – pituitary gland – Leydig cells axis. An Association ofGossypol treatment with Leydig cell hypo-function and decrease number of cellswas noticed for the male rat testosterone level. To our knowledge this is the firstreport of quantitative analysis of Leydig cell density in rat with Gossypoltreatment and it is suitable for clinical evaluation of testicular dysfunction.التأثر